An economic analysis of the Public Transport Regulation Act, 2009 - Barrett, Sean D. (Economic & Social Studies, 2011)
This paper analyses the Public Transport Regulation Act 2009, published on September 8, 2009. The Act provides for the regulation of public bus passenger services, changes the name of the Dublin Transport Authority to the National Transport Authority and abolishes the Commission for Taxi Regulation. The economic importance of the Act is that it retains the restrictions on new market entry to the bus sector and continues to subsidise the sector by direct award subsidies. The policy options foregone by the Act are the alternatives of competition in the market by independent bus operators and competition through competitive tendering to provide bus services where subsidies are deemed necessary.
Policy paper
Keywords: Public transportation; Regulation; Competition